RESPON SISWA TERHADAP MATERI PEMBELAJARAN IPS MELALUI OBJEK NYATA DI MI SABILAL MUHTADIN KAPUAS HULU - Sri Novita Sari (Lembaga Pengembangan Kinerja Dosen, 2022)
In the process of teaching and learning in schools conducted by subject teachers, of course, they experience various kinds of obstacles. This problem hit both students and educators which in the end caused the teaching and learning process to be not conducive. In addition to the non-conducive atmosphere during the learning process, it also results in difficulties for students to capture or accept the material provided by the subject teacher. Besides that, many teachers use the lecture learning method in learning, where the presentation of teaching is through explanations and oral narrative by the teacher to students about a material topic. The lecture method is considered a less effective method because it is a non-participatory monologue. Real or familiar objects that we see directly provide actions such as grasping and manipulation. This will shape the future neural processing for cognition, action and memory. This study aims to determine student responses to social studies learning by using real objects at MI Sabilal Muhtadin Kapuas Hulu. This can be seen from the increasingly solid understanding and student learning outcomes of the material presented by the teacher, learning completeness increased from each cycle I (68% ) Cycle II (88%). The conclusions through the results of this research show that the use of real objects can improve student learning outcomes.